Histomorphometric analyses of human adipose tissues using intact, flash-frozen samples. - Laforest, Sofia; Pelletier, Mélissa; Michaud, Andréanne; Daris, Marleen; Descamps, Justine; Soulet, Denis; Jensen, Michael D.; Tchernof, André (Histochemistry & Cell Biology, 2018)
Histomorphometric analyses of adipose tissue usually require formalin fixation of fresh samples. Our objective was to determine if intact, flash-frozen whole adipose tissue samples stored at − 80 °C could be used for measurements developed for fresh-fixed adipose tissues. Portions of adipose tissue samples were either formalin-fixed immediately upon sampling or flash-frozen and stored at − 80 °C and then formalin-fixed during the thawing process. Mean adipocyte diameter was measured. Immunohistochemistry was performed on additional samples to identify macrophage subtypes (M1, CD14 + and M2, CD206 +) and total (CD68 +) number. All slides were counterstained using haematoxylin and eosin (H&E). Visual inspection of H&E-stained adipose tissue slides performed in a blinded fashion showed little or no sign of cell breakage in 74% of frozen-fixed samples and in 68% of fresh-fixed samples (p > 0.5). There was no difference in the distribution frequencies of adipocyte sizes in fresh-fixed vs. frozen-fixed tissues in both depots (p > 0.9). Mean adipocyte size from frozen-fixed samples correlated significantly and positively with adipocyte size from fresh-fixed samples (r = 0.74, p < 0.0001, for both depots). The quality of staining/immunostaining and appearance of tissue architecture were comparable in fresh-fixed vs. frozen-fixed samples. In conclusion, intact flash-frozen adipose tissue samples stored at − 80 °C can be used to perform techniques conventionally applied to fresh-fixed samples. This approach allows for retrospective studies with frozen human adipose tissue samples.